Aligning assessment, learning and teaching in curricular reform and implementation - Murchan, Damian (National Council for Curriculum and Assessment, 2019)
This paper aims to present for discussion a number of issues that will be pertinent when considering the role of assessment in the redeveloped primary curriculum. As the NCCA have articulated, “in a climate of change, different stakeholders are making different assumptions about assessments” and “there is a need to articulate a clear vision for the assessment landscape.” This paper represents a first step towards articulating this vision. Six key questions have been posed by the NCCA, as follows: 1. What clear definitions or statements of assessment would provide clarity in the primary education system level? 2. What definitive principles of assessment should be promoted to support an outcomes based curriculum at primary level? 3. How can a theoretical framework for assessment enhance and promote greater teacher autonomy and agency in the context of a redeveloped curriculum? 4. How do we conceive standardised tests to avoid distortions or narrowing in the education process such as teaching-to-the-test and narrowing of the curriculum? (in the context of the 2007 continuum) 5. What is the rationale for designating or not designating domain specific assessment practices in a primary curriculum? 6. How or what is it that should be spotlighted when we think about a broad and balanced curriculum? These six questions will be addressed in turn. In responding to each question, we have made a conscious effort to contextualise our responses appropriately, in order to maximise the utility of the paper. That is, where possible, the discussion is mapped on to current thinking regarding assessment (garnered from a consultation of extant NCCA literature), and in light of existing government policies that have, and will continue to have significant implications for assessment practice. Finally, the main messages of the paper are consolidated and summarised.
PUBLISHED
Keywords: Primary education; Assessment; Curricular design; Making Ireland; EDUCATION; Education